Evaluation of Trace Element Levels and Antioxidant Metabolism in Cattle with Cutaneous Papillomatosis - Arslan, Handan Hilal; Tarhan, Duygu; Cenesiz, Sena; Alkan, Fatma Ates; Ozcan, Umit; Arslan, Esma Tongut; Barutcu, Umit Bora; Or, Mehmet Erman (Acta Scientiae Veterinariae, 2018)
Background: Cutaneous papillomas are benign proliferative neoplasms. The aetiology and pathogenesis of the disease are very complex. Papillomatosis lesions can be detected anywhere on the body, frequently appearing on the surface of the head, neck, teats, udder, external genital mucosa and upper part of the gastrointestinal tract. The disease is not life threatening but due to loss of productivity, owners often cull animals with papillomatosis. The relationships between trace elements, heavy metals and cancer are still researching. The aim of this study was the evaluation of the relationships between trace elements and antioxidant metabolism, and cutaneous papillomatosis, in cattle. Materials, Methods & Results: Eleven cattle with cutaneous papillomatosis and 10 healthy cattle constituted the study group and control group, respectively. Clinical examinations were performed on all animals. Blood samples were collected and Cr, Cu, Fe, Mg, Mn, Se, Zn, As, B, Ni, Si and Co levels were determined. The analyses were conducted with an inductively coupled plasma-optical emission spectrophotometer. In addition, catalase (CAT), glutathione (GSH), malondialdehyde (MDA) and ceruloplasmin (Cp) concentrations were measured. The Ni, Si and MDA levels of the study group were significantly higher than those of the control group (P < 0.05) but the Se levels of the study group were significantly lower than in the control group (P < 0.05). The normality of the data was determined with the Shapiro-Wilk Test and the Independent Samples t-Test or Mann-Whitney U test was used for statistical comparison of the groups. Discussion: Trace elements are essential components of biological systems. The levels of trace elements, such as Cu, Co, I, Se, Zn and Mn, which are affected by grazing activity, influence ruminants’ reproductive performance and other production parameters. The elements Al, As, Cr, Ni and Sn are also presumed to be essential for ruminant metabolism, although sufficient research data are not available. In the present study, Cr, Cu, Fe, Mg, Mn, Zn, As, B and Co levels were not significantly different between the papilloma and control groups. Se is an important trace element for skin health. This study revealed a mean serum Se level in animals with papillomatosis that was significantly lower than in the healthy group. Although the mode of anticancer activity of Se is not clear, some factors, such as antioxidant protection, improved immune system surveillance, carcinogen detoxification, modulation of cell proliferation and inhibition of tumour cell invasion and angiogenesis, are important. Ni is classified as a toxic heavy metal. In addition, it could be carcinogenic to humans. Ni level was two times higher in the papillomatosis group than in the healthy animals, in the present study. This result may indicate that Ni has a role in the genesis of papillomatosis in cattle. Si injection can cause inflammation, granulomas and cancer. There are few reports about Si levels in animals and the significant difference in the Si levels in cattle with cutaneous papillomatosis reported in this study may be a new indicator for the disease. The skin contains antioxidant molecules that include GSH, alpha-tocopherol or vitamin E, ascorbic acid or vitamin C, glutathione peroxidases, glutathione reductase, glutathione S-transferases (GSTs), superoxide dismutases (SODs), CAT and quinine reductase. There is strong interaction between ROS and/or their oxidant products and antioxidant molecules in the skin. In this study, although MDA levels were higher in the study group than in the control group, there was no significant difference between the groups in their CAT levels, and also in the GSH and CP levels. In conclusion, these results may evidence the systemic effects of papillomatosis on trace element levels and on oxidant metabolism in cattle.